2017
DOI: 10.1002/jcop.21860
|View full text |Cite
|
Sign up to set email alerts
|

Improving community readiness for change through coalition capacity building: Evidence from a multisite intervention

Abstract: Often, community coalitions are facilitators of community-level changes when addressing underage drinking. Although studies have shown that enhancing coalition capacity is related to improved internal functioning, the relationship between enhanced capacity and community readiness for change is not well established. The present study used a pretest-posttest design to examine whether enhancing coalition capacity through training and technical assistance was associated with improved community readiness and coalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 33 publications
1
51
0
1
Order By: Relevance
“…The authors reported that the number of interviews per community varied between one and 33 (mean = 7.3, SD = 5.9, median = 6, six studies provided no information on the number of interviews per community), with 15% of studies using less than the recommended four interviews per community. This is in line with studies published since 2013 that followed the recommendations of the CR handbook and conducted an average of four to eight interviews per community (e.g., in [15][16][17][18][19]). However, Kesten et al.…”
Section: Discussionsupporting
confidence: 87%
“…The authors reported that the number of interviews per community varied between one and 33 (mean = 7.3, SD = 5.9, median = 6, six studies provided no information on the number of interviews per community), with 15% of studies using less than the recommended four interviews per community. This is in line with studies published since 2013 that followed the recommendations of the CR handbook and conducted an average of four to eight interviews per community (e.g., in [15][16][17][18][19]). However, Kesten et al.…”
Section: Discussionsupporting
confidence: 87%
“…42 9. ábra: Az új szemléletből levezethető tevékenységek A közösség saját érdekeinek megfelelő és hatásos beavatkozásokhoz vezető döntésekre és a beavatkozások megvalósításra való felkészítését egyfelől a népegészségügyi szakemberek, másfelől a közösségfejlesztésben jártas szakértők együttes munkája tudja biztosítani. 43,44,45 Megjegyezzük, az adott közösségben élő szakemberek mellett indokolt lehet szakértők bevonása közösségen kívülről is. A közösségi egészségterv kidolgozásakor szakértők segítik az érintetteket az adott egészségproblémával kapcsolatos közös vélemény kialakításában, valamint a legjobb megoldások megfogalmazásában, és a szakmai kritériumoknak való megfeleltetésében, és hangsúlyozottan nem előre kidolgozott javaslatokat "szolgáltatnak".…”
Section: Tevékenységekunclassified
“…Training would license individuals based on work experience and test scores with quality upgrades over time. It helps communities build an implementation system to support prevention and treatment to include health and social services, schools, parent groups, businesses, law enforcement, and the judicial system (Ostaszewski et al 2018 ; Sumnall 2019 ; Watson-Thompson et al 2017 ).…”
Section: Emerging Success Stories In Prevention Sciencementioning
confidence: 99%